Combined plasma and tissue genotyping of EGFR T790M benefits NSCLC patients: a real‐world clinical example. Issue 5 (10th April 2019) - Wei, Bing; Zhao, Chengzhi; Li, Jun; Zhao, Jiuzhou; Ren, Pengfei; Yang, Ke; Yan, Chi; Sun, Rui; Ma, Jie; Guo, Yongjun
Abstract : Acquired resistance to epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitors (TKIs) is a prevalent clinical problem in the management of advanced non‐small‐cell lung cancer (NSCLC) with TKI‐sensitizing mutations in the EGFR gene. Third‐generation EGFR‐TKIs have demonstrated potent activity against TKI resistance mediated by the EGFR T790M mutation, and standard rebiopsy and liquid biopsy are utilized to assess the T790M status of the NSCLC patients who experienced progressive disease (PD). Here, we conducted a retrospective study to assess 375 patients whose initial biopsy indicated a TKI‐sensitizing mutation (either EGFR 19del or L858R) and who developed PD after treatment with first‐generation TKIs, and assayed for T790M status. We adopted a combination approach in which tissue rebiopsy is preferred, utilizing liquid biopsies when tissue rebiopsy is not feasible. We analyzed the potential predictive clinical factors affecting T790M detection, evaluated the standard rebiopsy and liquid biopsy methods in T790M genotyping, and reported the clinical performance of osimertinib. Our results suggested that primary EGFR 19del, brain metastasis, and longer progression‐free survival of initial EGFR‐TKI treatment are associated with acquired T790M resistance. T790M‐positive patients significantly benefited from osimertinib. In conclusion, the real‐world clinical adoption of the combination approach with both tissue rebiopsy and liquid biopsy for T790M genotyping may provide significant benefits to patients who have developed PD after first‐generation TKI treatments. Abstract : Acquired resistance to epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitors (TKIs) is a prevalent problem in the clinical management of advanced non‐small‐cell lung cancer (NSCLC) with TKI‐sensitizing mutations in the EGFR gene. Here, we analyzed the potential predictive clinical factors affecting EGFR T790M mutation detection. Our results suggested that primary EGFR 19del, brain metastasis, and longer progression‐free survival of initial EGFR‐TKI treatment are associated with acquired T790M resistance and that T790M‐positive patients significantly benefited from osimertinib.